Transmission of Local Wisdom: Ijazah of Magi Science in Santri the Salafiyah Islamic Boarding School Banten Indonesia - Sholahuddin Al Ayubi; Akhmad Marjuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines how the graduating process at the Salafiyah Islamic Boarding School in Banten, Indonesia, provides Santris with magical knowledge. In addition to providing religious instruction, pesantren is a site for the transmission of mystical and spiritual traditions based on Sufism and indigenous knowledge. The key subjects of this study include the different magical disciplines that are studied and used, the mystical experience of Santris, the complexity of the transmission of magical information, and the process by which kiai award certificates. The study uses a qualitative methodology through observation and in-depth interviews with Kiai and Santris in Banten's Serang and Pandeglang regions. The results of the study show that the transmission of magical knowledge is facilitated by a strong spiritual connection between kiai and Santris, with a certificate acting as a symbol of moral and spiritual legitimacy. This approach emphasizes moral development, mental readiness, and worship discipline in addition to cognitive mastery. The mystical Santris experiences, which include spiritual dreams, karomah experiences, and symbolic exchanges with teachers, are thought to be a part of the spiritual path leading to a closer relationship with God. The magical knowledge gained includes self-defense, medicine, safety, and the opening of sustenance within the framework of Islamic teachings. This study indicates that the continuation of the Islamic spiritual inheritance across the archipelago depends on salafiyah pesantrens, which combine Islamic normative teachings with indigenous knowledge and mystical experiences.